Simple And Safe Epileptic Seizures Monitoring System With Alarm - Mohd Hafifi Bin Mohd Zain, Mohd Hafifi (2010)
The aim of this project is to develop a simple and safe epileptic seizure monitoring system with alarm. Epilepsy is a condition in which a person has recurrent seizures.